Demonstration of IRI Data Library to Support Ghana’s Ag-Data Hub - Grossi, Amanda; Dinku, Tufa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
On March 21, 2022, the International Research Institute for Climate and Society (IRI) of the Columbia Climate School presented and demonstrated the capabilities and functionalities of the IRI Data Library during the Ghana Cluster Team Meeting in Accra, Ghana. The presentation and demonstration, which were organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, informed discussion and decisions around how to best develop a demand-driven ag-data hub for the country of Ghana.